الدور العلمي للمرأة المغربية في الحجاز من خلال كتاب الضوء اللامع للسّخاوي الجزء 12 - زبيدي فائزة; بوهني وفاء (جامعة الوادي university of eloued, 2025)
"تناولت هذه الدراسة موضوع الدور العلمي للمرأة المغربية في الحجاز خلال القرن التاسع هجري، من خلال كتاب شمس الدين السخاوي "" الضوء اللامع لأهل القرن التاسع الجزء 12. واعتمدنا في هذه الدراسة على المنهج الاحصائي والتحليلي لجميع العالمات المغربيات في كتاب الضوء اللامع الجزء 12، وقد انطلق هذا البحث من إشكالية: ما مدى اسهام المرأة المغربية في الحركة العلمية بالحجاز خلال القرن التاسع هجري، وللإجابة على هذه الإشكالية تضمن البحث ثلاث فصول: الأول خصص للتعريف بالسخاوي وحياته العلمية وآثاره واهمية كتابه أما الفصل الثاني فتضمن الحركة العلمية بالحجاز من خلال نشاط المؤسسات التعليمية والعلوم التي تدرس في تلك الحقبة، اما الفصل الثالث فهو أساس الدراسة التطبيقية بإحصاء عدد العالمات المغربيات في كتاب السخاوي وتحليلها عبر جداول ودوائر نسبية، المراءة المغري بية في الحجاز وطرق تحصيلها العلمي وحضورها الملفت في النشاط العلمي، ويظهر ذلك من خلال تبادل الاجازات مع علماء المشرق الإسلامي وما توصلنا ايه ان النساء المغربيات كان لهن حضور بارز فينشر العلم من خلال التدريس وحضور مجالس العلماء حتى كان علماء الرجال يتنافسون لأخذ الإجازات منهن وصاحب كتاب الضوء اللامع واحد منهم. "This study addresses the scientific role of Moroccan women in the Hijaz during the 9th century AH, through the twelfth volume of Shams al-Din al-Sakhawi’s book ""Al-Daw’ al-Lami‘ li-Ahl al-Qarn al-Tasi‘"" (The Shining Light on the People of the Ninth Century). We relied in this study on both statistical and analytical methods to examine all the Moroccan female scholars mentioned in Volume 12 of Al-Daw’ al-Lami‘ The research is guided by a central question: To what extent did Moroccan women contribute to the scientific movement in the Hijaz during the 9th century AH? To answer this question, the study is divided into three chapters: • The first chapter is dedicated to introducing al-Sakhawi, his scholarly life, his works, and the significance of his biographical dictionary. • The second chapter focuses on the scientific life in the Hijaz during that period, highlighting the activities of educational institutions and the types of sciences taught at the time. • The third chapter forms the core of the applied study. It includes a statistical survey of Moroccan female scholars mentioned in al-Sakhawi’s book, analyzed through tables and pie charts. This chapter also discusses how these women acquired knowledge and their remarkable presence in the scientific sphere. Their engagement is evident through the exchange of ijazat (teaching authorizations) with scholars from the Islamic East. The study concludes that Moroccan women had a prominent presence in disseminating knowledge through teaching and participating in scholarly gatherings. Male scholars, including al-Sakhawi himself, were often eager to obtain ijazat from them, which reflects the high scholarly status these women held "
مذكرة ماستر قسم علوم الانسانية تخصص تاريخ وسيط
Keywords: القرن التاسع الهجري; السخاوي; الضوء اللامع; الحجاز; المراة المغاربية; Maghrebi women; Hijaz; Shining Light; Al-Sakhawi; 9th century AH